Decimal reduction times of Bacillus spores in fermented fish paste - Nunez, Andrea Tan (2007)
ABSTRACT This study was conducted to establish the D80°C and D85°C values of Bacillus spores in fermented fish paste or bagoong. The physicochemical properties and proximate composition of the sample were determined prior to heat resistance studies. Results showed that the % NaCl content at 28.62 ± 0.80 was found to be higher than the minimum requirement, while, the moisture and protein content at 60.8918 ± 0.24 and 8.44 ± 1.73, respectively, showed values lower than the normal ranges. These differences in physico-chemical characteristics affected the resulting D-values for the treatments. The D80°C and D85°C values were calculated to be 1.0742 ± 0.0232 and 0.9612 ± 0.1247, respectively, which provide effective destruction of most Bacillus spores in bagoong. The results of this study may be used as baseline information for controlling measures in the thermal processing of bagoong against the reference strains, such as Bacillus sphaericus and Bacillus